Market Potential for "The Hindu" in Urban and Semi Urban Areas - Sivakumar, N.; Raghunatha Reddy, D. (Indian Journal of Marketing, 2005)
The study is carried out for "The Hindu" at Hyderabad and Anantapur. The company started in 1878 as weekly, and has become a daily in commission and printing. It is printed in ten centers apart from the main edition at Chennai, where the corporate office is based. The printing centers at Coimbatore, Bangalore, Madurai, Hyderabad, New Delhi, Vishakapatnam, Thiruvanathapuram, Kochi, Vijayawada and Mangalore. All this centers are connected with high-speed data lines for news transmission across the country. Newspapers now days have become one of the most important source of information for a reader to know the things in depth. No doubt other media vehicles like Television and other sources provide information but they lack the inner course of action wanted by the reader. There is a high competition between the English dailies in the state after the emergence of "The Times of India" in Andhra Pradesh. This made "The Hindu" to retain its hold in the market and to come with different strategies. This study has given some scope to find different aspects for The Hindu in Urban and semi urban areas.